2017
DOI: 10.5923/j.ijme.20170706.03
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Impact and Tensile Properties of Recycled Polypropylene

Abstract: The present research proposed to evaluate the tensile and impact properties of polypropylene originating from secondary recycling. The polymer chosen for the studies was polypropylene (PP) for its high application and availability. The tensile and impact tests were performed on virgin polypropylene, recycled polypropylene and mixtures of different proportions of both. Thus, for each sample, values of yield strength, elastic modulus, yield elongation and impact strength were obtained. The results of the average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…As an example, several studies have reported that the mechanical properties of recycled plastic, especially when originating from HHW, were reduced when compared to virgin plastic. This includes tensile strength and elongation to break for recycled PP (Dahlbo et al, 2018), tensile strength of recycled HDPE (Luijsterburg and Goossens, 2014;Chariyachotilert et al, 2006), elongation to break for recycled LLDPE (Al-Salem, 2019), and impact strength of recycled PP (Barbosa et al, 2017). These changes in properties might be caused by thermal-mechanical degradation of the polymer during reprocessing, degradation during the lifetime, mainly due to photo oxidation processes (Ragaert et al, 2017), and/or contamination of the plastic waste, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, several studies have reported that the mechanical properties of recycled plastic, especially when originating from HHW, were reduced when compared to virgin plastic. This includes tensile strength and elongation to break for recycled PP (Dahlbo et al, 2018), tensile strength of recycled HDPE (Luijsterburg and Goossens, 2014;Chariyachotilert et al, 2006), elongation to break for recycled LLDPE (Al-Salem, 2019), and impact strength of recycled PP (Barbosa et al, 2017). These changes in properties might be caused by thermal-mechanical degradation of the polymer during reprocessing, degradation during the lifetime, mainly due to photo oxidation processes (Ragaert et al, 2017), and/or contamination of the plastic waste, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the experiment results with prior research studies revealed that WPS tensile strength was 20-40% lower compared to the injection pellet recycled polypropylene around 19 -22.3 MPa reported in [7], [24], [27]. In addition, the tensile strength of WPB only reaches half the tensile capability compared to the reported compression molded powder recycled HDPE with 22 -25 MPa with approximately 100% elongation at break [5], [26], [28].…”
Section: Experiments Resultsmentioning
confidence: 56%
“…PP is a recyclable and reusable material, so its life cycle does not end with producing a final product [1,2]. When subjected to tension, recycled PP exhibits similar mechanical characteristics (elastic limit and elastic modulus) as transparent virgin PP, and therefore, it can be used as widely as any non-recycled material, and even has certain advantages such as lower cost and a contribution to environmental protection [3][4][5]. Polypropylene has high chemical resistance and excellent resistance (no attack) to most acid solutions, alcohols, bases and mineral oils [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%